Reconstitution of political anthropology. heteronomies between political science and anthropology (2014)
As an anthropologist, I intend to develop some reflections over the field of study of political science, in dialogue with the intellectual horizon set by Eric Voegelin and in a critical relation with the ideas expressed about political science in the recent publications, of professors Andrés Casas and Rodrigo Losada, whom represent an important school of thought in the study of the political phenomena. The debate is framed in terms of dialogue between reductive visions and heuristic approaches. It is stated the importance of the theoretical category of experience of order as a connecting pattern between anthropology and political science and allowing them to enrich their rhetorical scientific universe in terms of identifying the complexity of the political phenomenon.